2015
DOI: 10.1038/ja.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial evaluation of some teicoplanin pseudoaglycon derivatives containing alkyl- and arylthiosubstituted maleimides

Abstract: Dedicated to the memory of Professor Maria N Preobrazhenskaya ✠ Bis-alkylthio maleimido derivatives have been prepared from teicoplanin pseudoaglycon by reaction of its primary amino group with N-ethoxycarbonyl bis-alkylthiomaleimides. Some of the new derivatives displayed excellent antibacterial activity against resistant bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Teicoplanin, vancomycin, oritavancin, and chloramphenicol (Sigma-Aldrich, Germany); dalbavancin (MedChemExpress, Sweden); MA79 (Csávás et al, 2015), ERJ390 (Pintér et al, 2009), and SZZS-12 (Szucs et al, 2017); carbenicillin, gentamicin and erythromycin (Duchefa Biochemie, Netherland); vancomycin BODIPY-FL conjugate (Thermo Fisher Scientific, Germany) and fluorescently labeled teicoplanin (Vimberg et al, 2019).…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teicoplanin, vancomycin, oritavancin, and chloramphenicol (Sigma-Aldrich, Germany); dalbavancin (MedChemExpress, Sweden); MA79 (Csávás et al, 2015), ERJ390 (Pintér et al, 2009), and SZZS-12 (Szucs et al, 2017); carbenicillin, gentamicin and erythromycin (Duchefa Biochemie, Netherland); vancomycin BODIPY-FL conjugate (Thermo Fisher Scientific, Germany) and fluorescently labeled teicoplanin (Vimberg et al, 2019).…”
Section: Antibioticsmentioning
confidence: 99%
“…The ability of the E. faecium vanZ Tei and vanZ g paralogs to confer resistance to glycopeptide antibiotics was tested in S. aureus, which naturally does not encode any proteins of the VanZ superfamily. In particular, we determined the susceptibility of S. aureus RN4220 expressing vanZ Tei and vanZ g to the clinically used glycopeptide antibiotic vancomycin (VAN); the lipoglycopeptide antibiotics teicoplanin (TEI), oritavancin (ORI), and dalbavancin (DALB); and three experimental lipoglycopeptide antibiotics derived from teicoplanin pseudoaglycone: MA79 (Csávás et al, 2015), ERJ390 (Pintér et al, 2009) and SZZS-12 (Szucs et al, 2017; Figure 1). In addition, the non-glycopeptide antibiotics carbenicillin (CARB, cell wall-targeting) gentamicin (GEN, 30S ribosometargeting) and erythromycin (ERY, 50S ribosome-targeting) were used as controls.…”
Section: Glycopeptide Antibioticsmentioning
confidence: 99%
“…These include the conjugation with a squaric acid moiety, isoindole formation and the incorporation of variously substituted maleimides. [10][11][12] Many of these compounds showed good in vitro activity against various bacteria, including VRE, and interestingly, some of them proved to be efficient against different strains of influenza virus.…”
Section: Introductionmentioning
confidence: 99%
“…37 The logP calculations for the whole collection of compounds revealed that all of them are lipophilic compounds with logP values close to or 43. Based on the results presented here and in our previous articles, [16][17][18][19][20][21]27,28 it seems that there is no linear correlation between the lipophilicity of glycopeptide antibiotics and their antibacterial activity against VRE strains, but the presence of a hydrophobic moiety on the antibiotic is critical in most cases.…”
Section: Resultsmentioning
confidence: 49%